EQUIVALENCE AND CULTURAL ADAPTATION IN THE TRANSLATION OF HISTORICAL REALITIES - Jalilova Dilbar Mansur qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. The translation of historical realities requires a careful balance between equivalence and cultural adaptation to preserve the meaning, context, and cultural significance of historical concepts. Historical terms, social institutions, traditions, and cultural references often reflect unique features of a particular period and society, creating challenges for translators. This article explores the role of equivalence and adaptation strategies in transferring historical realities from one language and culture into another. It focuses on how translators maintain historical authenticity while making texts understandable for target readers. The study highlights the importance of cultural awareness, contextual analysis, and appropriate translation choices in representing historical elements accurately.